ANALISIS TERHADAP PERTIMBANGAN HAKIM DALAM MEMUTUSKAN PERKARA PERCERAIAN KARENA NUSYUZ ISTERI (Studi Kasus pada Putusan Perkara Nomor 0391/Pdt.G/2014/PA.Bn dan 8/Pdt.G/2015/PTA Bn) - Rosmawati, Rosmawati (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
The considerations of the Panel of Judges  in the first instance of the courts (High Religious Court of Bengkulu) are: 1) Frequent quarrels and quarrels between  husband and wife are not solely due to the mistakes of the wife, but also because there is no mutual  understanding between  the two parties.  2) The evidence  submitted in the form of photographs and  statements of witnesses is not sufficient to prove the behavior of nusyuz of the wife because it is not equipped with other supporting evidence.3) Criminal acts of corruption committed  by the wife can not be used as the basis of the assessment that the concerned has acted and behave nusyuz, not directly related to the rights and duties between  husband and wife in household affairs. 4) The wife likes to indebted to a third party without the knowledge  of her husband can not necessarily be the legal basis that the concerned has acted nushyuz. Because  there is only one evidence  that explicitly indicates that the concerned has paid off the wife’s debts, while other evidence  shows the wife who has paid off its own debts.  5) The occurrence of separation of residence between  husband and wife is not because the wife has left the place of residence without the applicant’s / appealed permission,  but the separation of the applicant’s / appellate residence has surrendered his wife to his parents  in a kinship and good manner. 6) During the sepa- ration of the house  because of repatriation to the home  of her parents, the wife remains  obedient to the wishes of the applicant/ comparable is to remain  settled in the home  of his parents. 7) The wife as the plaintiff of reconvention is not proven  to act and behave nusyuz as the opinion  of the court of first instance.  So that he remains  legally entitled to get the rights as a devout  wife to the husband. 8) During the separation of the husband’s dwelling only performs  the obligation  as a father to his childre.that is transfer to the savings account of his children.  Second, in terms of the jurisprudence